An Investigation on The Effect of Professional Training On Journalism Ethics in Uganda - Ayebazibwe, Kukundakwe Esther (Kabale University, 2023)
The debate on whether professional training is relevant for journalism practice has been existing, with some proposing that it is an art developed through talent and practice (Parks, 2012). Despite the efforts in training, one cannot certainly say that proper training leads to professional journalism practice. Through in-depth interviews and questionnaires, this study seeks to find out the role of professional training on the respect for journalism professional ethics. The analysis shows some of the differences in ethical perceptions between the trained and untrained journalists. The discussion on the challenges faced by journalists in Uganda reveals that journalists across the world are faced with similar challenges although their media systems and cultures may differ. Although other factors cannot be completely ruled out, the study concludes that good training affects ethical perceptions of journalists leading to better professional quality, which means that training is an important attribute in media practice. However, it also observes that there are some other factors that can affect quality journalism aside training. It recommends that all stakeholders in the media industry (media houses, media practitioners, training institutions, professional associations and government) should all work together to promote quality journalism in Uganda.